14.5k views
4 votes
Solve the equation.
11-(x+5) = 8x - 3

User Halfgaar
by
5.8k points

2 Answers

7 votes

Answer:

11-(x+5) = 8x - 3

opening up the brackets,

11-x -5= 8x -3

6-x= 8x-3

bringing the x over to the other side of the equation,

6= 8x -3 +x

6= 9x-3

bringing the -3 to the other side of the equation,

6+3= 9x

9x= 9

x=1

User Qin
by
6.3k points
3 votes

Answer:

1

Explanation:

11-x-5=8x-3

6-x=8x-3

Combining similar terms

6+3=8x+x

9=9x

Dividing both sides by 9

1=x

OR

x=1

User Jitendra Singh
by
5.5k points